Profiting from Punishment: Public Education and the School Security Market - Simmons, Lizbet (Social justice, 2014)
The article discusses the relationship between public education and the school security market in America as of 2015, and it mentions the punitive nature of public schools in the U.S., shared leadership and funding, and the structural forces shaping a correctional approach in education. The economic aspects of punishment are examined, as well as racialized youth punishment and the penal state's impacts on the social welfare principles of public schooling in the U.S.